KARAKTERISTIK TIPOLOGI ARSITEKTUR KOLONIAL BELANDA RUMAH BASTION BENTENG FORT ORANJE DI TERNATE - Endah Harisun; M Amrin MS Conoras (Journal of Science and Engineering, 2018)
Ternate Region which was once the center of European power in the archipelago before being transferred to Jakarta by Governor-General Jan Pieterzen Coen. (1619-1623), who later renamed Batavia, was the V.O.C (Dutch East Indian Company) headquarters, the world's first multi-national company, for Southeast Asia centered on the Orange fortress Ternate. Orange fortress built by Cornelis Metalief de Jonge in 1606-1609. V.O.C. which recorded putting his governor in Ternate as many as 55 people from 1607 to 1810, depart from this history so up to now, the existence of Dutch buildings in the city of Ternate can still be found. The method used in this research, is a qualitative descriptive method that focuses on the overall description of the form, function, and periodization associated with the legacy of the Dutch Colonial Architecture in Ternate. The existence of colonial architectural heritage in Ternate becomes very important to maintain the existence of Ternate as one of the regions that have historical value in Indonesia. In order to support it, this research process becomes very important for the development of architectural science in Ternate City and the general contribution of this research is expected to complete the documentation about the development of the city of Ternate not only in terms of its history but in terms of its architectural wealth